On the Origin of Useful Concept in the Marxist Thinking of the Young Croce (1893-1897) - Della Pelle, Piergiorgio (Bollettino Filosofico, 2025)
The philosophy of the Spirit, developed by Benedetto Croce during his mature years of thought, has one of its distinctive features in the category of the Useful. For this reason, critics have tried to give answers about the origin of this idea within his youthful thought. Considering the main existing hypotheses (the Machiavelli/Marx parallelism and the 1900-1901 public debate with Pareto), a new one is here proposed moving from the science concept developed since 1893 by a young neo-Kantian Croce and from his studies on Marxist theory and pure economics (1895-1897). Keywords: Croce, Economics, Marx, Neo-Kantianism, Useful